Polycaprolactone fibrous electrospun scaffolds reinforced with copper doped wollastonite for bone tissue engineering applications - Abudhahir, Mohamed; Saleem, Azeena; Paramita, Pragyan; Kumar, Sukumar Dinesh; Tze‐Wen, Chung; Selvamurugan, Nagarajan; Moorthi, Ambigapathi (Journal of biomedical materials research. Part B, Applied biomaterials, 2021)
The bone defects healing are always associated with post implantation infections; hence biomaterials rules significant role for orchestration of defective bone. In this study, we synthesized biocomposite scaffold by combining polycaprolactone (PCL), wollastonite (Ws) and metal ions (Cu) by electrospinning technique. The manufactured scaffolds (PCL/Ws andPCL/Cu–Ws) were subjected to physio‐chemical characterization by scanning electron microscopy, energy dispersive X‐ray spectroscopy, Fourier Transform Infra Red Spectroscopy (FTIR) and XRD. The surface topography of the scaffolds was found to be micro‐fibrous in nature and each fiber was cylindrical in structure. The exogenous biomineralization and protein adsorption capacity of these scaffolds were studied. Enhanced amount of protein was adsorbed on PCL/Cu‐Ws than PCL/Ws scaffold after incubating for 48 hr in foetal bovine serum (FBS) also the biomineralization shown to be promoted the apatite formation in vitro. The synthesized PCL/Cu–Ws scaffold was biocompatible to mouse mesenchymal stem cells and enhanced the mRNA expressionof osteoblastic specific marker genes including alkaline phosphatase and type I collagen and major transcription factor Runx2 in the presence of osteogenic medium indicates the osteoconductive nature of the scaffolds. The amount of calcium deposition and promotion of osteoblast differentiation and mineralization on human osteoblast cells was confirmed by alizarin red staining. The fabricated scaffolds possess potent antibacterial effect against Staphylococcu aureus and Escherichia coli. Hence, our outcomes confirmed that the PCL/Ws and PCL/Cu–Ws scaffolds promote bonesynthesis by cell proliferation and differentiation suitable for applications in bone regeneration orbone defects.